Phase I Study of Cisplatin, Hyperthermia, and Lapatinib in Patients With Recurrent Carcinoma of the Uterine Cervix in a Previously Irradiated Area. (6th February 2015) - Meerten, Esther; Franckena, Martine; Wiemer, Erik; Doorn, Lena; Kraan, Jaco; Westermann, Anneke; Sleijfer, Stefan
Abstract: Author Summary: Background: Patients with recurrent cervical cancer in a previously irradiated area might benefit from cisplatin combined with hyperthermia. Lapatinib inhibits the intracellular tyrosine kinase domain of the epidermal growth factor receptor (EGFR) and HER2. Overexpression of EGFR and HER2 is frequently seen in patients with cervical cancer and is potentially involved in chemotherapy resistance. In addition, preclinical data suggest a synergistic effect of combining cisplatin and lapatinib. Consequently, this phase I dose-escalation study was performed to determine the maximum tolerated dose (MTD) of lapatinib added to fixed doses of cisplatin and hyperthermia. Methods: Eight patients with previously irradiated recurrent cervical carcinoma were enrolled and scheduled for 6 weekly administrations of 70 mg/m 2 cisplatin combined with locoregional hyperthermia. Hyperthermia consisted of the achievement of intraluminal temperatures of 40–43°C as homogeneously as possible over 60 minutes. Daily lapatinib was added on days 1–56, starting with a dose level of 1, 000 mg. The MTD was defined as the highest dose at which ≤1 of 6 patients experienced dose-limiting toxicity (DLT). DLT was defined as grade 4 neutropenia lasting >7 days, febrile neutropenia grade ≥3, grade 4 thrombocytopenia, grade ≥2 renal toxicity, postponement of cisplatin and hyperthermia for ≥2 weeks, or grade ≥3 nonhematologic adverse events except for nausea or vomiting, diarrhea, or skin toxicity, for which the following DLT definitions were applied: grade ≥3 persistent nausea or vomiting or diarrhea despite optimal medical treatment or grade 4 skin toxicity. Safety, pharmacodynamics, and response were assessed. Results: The first two patients of both the 1, 000- and 750-mg dose level experienced DLTs. Of the four patients treated at dose level −2 (500 mg), only one patient was able to complete the treatment as planned, two patients experienced a DLT, and one patient was not evaluable because of early progressive disease. In the evaluable patients, one patient with progressive disease, four patients with stable disease, and two patients with partial response were observed. One patient with a partial response had a resection of the local recurrence. Pathological analysis showed a complete pathological response. Enumeration of circulating endothelial cells measured at baseline and during therapy did not show consistent results. The same applied for the pharmacodynamic effects on Ki-67, p27Kip1, and EGFR in pretreatment and on-therapy skin biopsies. Conclusion: It is not feasible to combine lapatinib with fixed doses of cisplatin and hyperthermia in patients with recurrent cervical carcinoma in a previously irradiated area mainly because of increased cisplatin-related toxicity. The observed complete pathological response is intriguing and warrants further investigation of combinations consisting of HER2 blockade and cisplatin plus hyperthermia.